Nephropathy in Diabetic Patients and Anemia Their Relationship - Alijonov D.A. student; Bektasheva G.M. student; Kholmatova G.A. PhD (Peerian Journals Publishing, 2023)
Diabetes mellitus (DM) is the most common endocrine disease, which in the last decade has been called a worldwide non-communicable epidemic: by 2025, it is expected that the number of patients with DM will exceed 300 million people. This means that late complications arising from metabolic disorders caused by hyperglycemia will also grow. It is well known that the duration and quality of life of patients with diabetes are determined by the development and progression of complications of diabetes.
Keywords: diabetes mellitus; microangiopathy; endocrine disease